Ответы и объяснения

2012-11-14T21:30:32+04:00

(х/y - y/x):(х - у) = x/y -y/x (домножаем) = (получается) x^{2} - y^{2}

                                                                                       ____________ =

                                                                                                xy 

 

= (x - y) (x + y)                                             (x - y)(x + y)                                 

   ___________  : (x - y) (домножим на xy) = ___________ (сокращаем x - y) = 

          xy                                                         xy (x - y)

 

= x + y

  _____

     xy